2016
DOI: 10.5603/piap.2016.0008
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors and Asthma in India—A Case-Control Study

Abstract: The present study concluded increased TV watching, increased mental stress, reduced hours of physical activity and travel may be correlated with asthma in India. With growing evidence of increasing association of asthma and sedentary lifestyle, it is imperative to reduce acquaintance to as well as incidence of these factors through public health policies, which may impact prevalence of asthma in Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Such effects would positively impact the quality of life of those affected. 2,3 Although having a television in the bedroom proved to be a protective factor against asthma, screen time did not differ between groups. The authors understand that such finding would be more relevant if associations with SB and the total screen time had also been found, which was analyzed both as continuous and categorical in nature.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such effects would positively impact the quality of life of those affected. 2,3 Although having a television in the bedroom proved to be a protective factor against asthma, screen time did not differ between groups. The authors understand that such finding would be more relevant if associations with SB and the total screen time had also been found, which was analyzed both as continuous and categorical in nature.…”
Section: Discussionmentioning
confidence: 94%
“…1 Such diseases are associated with children's inappropriate habits, such as reduced physical activity (PA) and increased time of sedentary behavior (SB), thus favoring overweight and childhood obesity. 2,3 According to data from the National Scholar Health Survey (Pesquisa Nacional de Saúde do Escolar -PeNSE), Brazilian adolescents account for the highest worldwide prevalence of asthma (23.2%). 4 Conversely, in children, the prevalence of asthma and allergic rhinitis is 24.3 and 12.6%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Asian countries, meta‐analysis showed that obesity (>30 kg/m 2 ) was associated with an overall increased risk of asthma by 2.02‐fold ( n = 8 studies) 27 . Sedentary behaviours such as increased TV watching, and reduced hours of physical activity have found to be correlated with asthma risk 43 . However, it is still unclear whether asthma predisposes an individual to obesity, if obesity confounds asthma diagnosis, or that both asthma and obesity simply co‐occur or interact.…”
Section: Risk Factors Of Asthmamentioning
confidence: 99%
“…27 Sedentary behaviours such as increased TV watching, and reduced hours of physical activity have found to be correlated with asthma risk. 43 However, it is still unclear whether asthma predisposes an individual to obesity, if obesity confounds asthma diagnosis, or that both asthma and obesity simply co-occur or interact. Obese individuals with asthma are more likely to have Th1-skewed inflammatory responses, which is in part mediated by insulin resistance, systemic inflammation and/or alterations in lipid metabolism.…”
Section: Lifestyle/individual Factorsmentioning
confidence: 99%
“…In the last few decades an altered eating pattern has been associated with asthma not only in the Indian adult population 6 but also among children and adolescents with major portion of their meals comprising of fried foods and fast foods which are loaded with energy and fats with a significant amount of saturated fat, cholesterol and sodium 7 . Fast foods have been taking a toll over the health of children because they replace the healthier food options such as fruits, vegetables, milk, breads and cereals 8 causing a suboptimal dietary intake of vitamins such as A, C, E and carotenoids as well as other antioxidants such as selenium and flavonoids which have an adverse effect on the modulation of oxidative lung stimuli.…”
Section: Introductionmentioning
confidence: 99%